The reaction of pea’s plants pro-antioxidant system on biostimulants stimpo and regoplant treatment - Kolesnikov, Maksym; Paschenko, Yuliia (My University, 2017)
Peas (Pisum sativum L.) are one of the main leguminous plants grown in Ukraine. The sown square of peas is 0,3 min. ha and 25% of them is in stepp. Peas are very light-, water- and soil-demanding culture, that’s why not realize its genetic productivity potential under adverse environmental conditions, owing to photosynthetic and photophosphorylation processes malfunctioning, changing in water state and development of oxidative defence. The usage of growth regulators normalize the metabolism and increase the crop production. The antioxidant system is very important for plant adaptation, and biostymulants Stimpo and Regoplant increase the plants stress resistance. The aim of presented work was to determine the impact of bioregulators Stimpo and Regoplant on the peroxidation processes, changes of antioxidant enzimes activity, proline content during peas onthogenesis under the conditions of South Steppe of Ukraine.
Keywords: рeas; plants; soil-demanding culture; genetic productivity; potential; regulators; peroxidation processes; oxidation